Development of an E-Book on Measurement, Quantities, And Units to Improve Digital Literacy of Grade X Students - Titin Takke Rannu; Heru Kuswanto (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2026)
This study aims to develop a Contextual Teaching and Learning (CTL)-based e-book integrated with digital literacy on the topic of measurement, quantities, and units to improve students' digital literacy. The research employed the Research and Development (R&D) method using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The subjects of this study were Grade X students of SMAN 1 Sekatak, who were divided into an experimental class and a control class. The research instruments included a digital literacy questionnaire and validation sheets, which had been tested for validity and reliability. The validity test results showed that all instrument items were valid, with very high reliability (Cronbach’s Alpha = 0.874). The implementation results indicated a significant improvement in digital literacy in the experimental class compared to the control class. The average score of the experimental class increased more significantly after the use of the CTL-based e-book. In addition, the evaluation results showed that the e-book was practical, with a reliability value of 0.709, and received positive responses from students. These findings indicate that the CTL-based e-book integrated with digital literacy is valid, practical, and effective in improving students’ digital literacy and in supporting more contextual and meaningful physics learning.